Econometric Analysis of Social Issues (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the realm of econometric analysis to unravel the complexities of pressing social issues. Focused on the intersection of economics and social dynamics, the piece explores how econometric methods are employed to dissect and understand issues such as income inequality, educational attainment, healthcare access, and environmental sustainability. By examining empirical studies and theoretical frameworks, the article illuminates the methodologies and challenges inherent in conducting econometric analyses of social phenomena.